Visual Impairment and Ataxia after Excision of Recurrent Cerebellar Space Occupation: A Case Report - Lixia JIN; Gang LIU; Junfa WU; Kewei YU; Xinwei TANG; Yi WU (康复学报)
Objective:To investigate the treatment of visual impairment and ataxia after excision of recurrent cerebellar space occupation.Methods:One pediatric patient had visual impairment and ataxia after excision of recurrent cerebellar space occupation. After clear diagnosis and etiology analysis, comprehensive rehabilitation treatment was applied, including physical therapy, speech training, swallowing training, balance function training, etc. Clinic effect was observed.Results:The pediatric patient had ataxia (cerebellar) with dysarthria, left eye vision loss, and right eye temporal field defect after excision of recurrent fourth ventricle cerebellar hair cell astrocytoma. The decrease in visual acuity could be caused by ischemic optic neuropathy caused by ischemia-reperfusion, or by optic atrophy caused by intracranial hypertension. After comprehensive rehabilitation treatment, the swallowing function, speech function, balanced function and the daily life function improved significantly, while the improvement of vision loss was not obvious.Conclusion:Comprehensive rehabilitation therapy is effective for the treatment of visual impairment and ataxia after excision of recurrent cerebellar space occupation. It mainly improves the balance motor function, while the improvement of vision is not obvious.